(untitled) (The Research of Medical Science Review, 2025)
Objective: To determine the frequency of Vitamin D deficiency in children with severe acute malnutrition. Methods: A cross-sectional study was conducted in the Department of Pediatric Medicine at Ghulam Muhammad Mahar Medical College (GMC), Sukkur, from 1st August 2024 to 31st January 2025, following ethical approval from the Institutional Review Board of GMC Sukkur. A total of 104 children aged 6 to 59 months, meeting the WHO criteria for severe acute malnutrition (SAM), were enrolled using non-probability consecutive sampling. Serum vitamin D deficiency was assessed by measuring 25-hydroxyvitamin D levels below 20 ng/mL using the electrochemiluminescence (ECL) method. Children with metabolic disorders, chronic kidney or liver disease, or those on vitamin D supplementation in the past three months were excluded. Demographic data, including age, gender, residence (urban/rural), immunization status, parental education, and socioeconomic status, were collected via a structured questionnaire. Anthropometric measurements of weight and height were taken with standardized equipment. Data were analyzed using SPSS version 29.0, and statistical significance was set at p ≤ 0.05. Results: Out of 104 children with severe acute malnutrition (SAM), 64 were males (61.5%) and 40 were females (38.5%). The mean age was 30.56 ± 15.03 months, with a mean weight of 12.74 ± 2.59 kg and a mean height of 87.52 ± 10.80 cm. Regarding demographics, 48.1% of children resided in urban areas, while 51.9% lived in rural settings. Immunization status was equally divided, with 50% having completed their immunizations. Vitamin D deficiency was found in 56.7% of the children. In terms of parental education, the largest group had intermediate education (26.0%), followed by primary (16.3%), matriculation (16.3%), secondary (15.4%), graduation (13.5%), and illiteracy (12.5%). Socioeconomic status showed that 39.4% were from lower, 31.7% from middle, and 28.8% from upper classes. Further analysis revealed significant associations between vitamin D deficiency and several factors. Females (72.5%) had a higher deficiency rate compared to males (46.9%, p = 0.010). Rural children had a higher deficiency rate (66.7%) than urban children (46%, p = 0.034). Children with incomplete immunizations had higher deficiency (67.3%, p = 0.029). Parental education was also significant, with lower-educated parents linked to higher deficiency rates (p = 0.014). No significant association was found with socioeconomic status (p = 0.903). Conclusion: This study shows a high prevalence rate of vitamin D deficiency in children with SAM, which was strongly associated with sex, rural place of residence, incomplete immunization, and lower parental education. These results are also consistent with other literature in Pakistan and comparable environments, emphasizing the importance of routine vitamin D screening and supplementation in malnourished children. Correction of this deficiency might benefit and salvage the recovery of these neonates, as well as lessen the associated long-term developmental morbidity in this susceptible population.